Effect of Geometries on the Natural Frequencies of Pratt Truss Bridges. (2015) - Widjajakusuma, Jack; Wijaya, Helen
Abstract: Pratt type truss bridges are in human history since 1844 through the early twentieth century and until today. The bridges are built all over the world and the materials were developed from wood and iron to iron and eventually to steel. In this paper, the natural frequencies and mode shapes of Pratt type truss bridges are determined. The changes of these natural frequencies with respect to parametric changes, such as spans and the kind of support connections, in the bridge are analyzed. These vibrational parameters can be used to detect the damage of the truss bridges and they are also fundamental to the solution of its dynamic responses due to seismic, wind and traffic loads. This paper gives the numerical values of natural frequencies as assessment values of a bridge's state of health.